Significant Genetic Impacts Accompany an Urban Rat Control Campaign in Salvador, Brazil - Richardson, Jonathan L.; Silveira, Georgianna; Soto Medrano, Ivanna; Arietta, A. Z.; Mariani, Carol; Pertile, Arsinoê C.; Carvalho Pereira, Ticiana; Childs, James E.; Ko, Albert I.; Costa, Federico; Caccone, Adalgisa (Frontiers in Ecology and Evolution, 2019)
Rats thrive in human-dominated landscapes, and have expanded to a near global distribution. Norway rats (Rattus norvegicus) contaminate food, damage infrastructure, and are reservoirs for zoonotic pathogens causing human diseases. To limit these negative impacts, entities around the world implement intervention and control strategies designed to quickly and drastically reduce the number of rats in a population. While the primary goal of these interventions is to reduce rat numbers and their detrimental activities, there are important, yet unexplored, population genetic implications for these rapid population declines. Here, we compare the population genetics of R. norvegicus before, immediately after, and several months following a rodenticide-based eradication campaign targeting rats in an urban slum of Salvador, Brazil. This slum has been the focus of long-term research designed to understand and reduce the risk of leptospirosis to people in this area. We also look for a clear source of rats contributing to population recovery by either rebound through breeding of local survivors or by immigration/reinvasion of the site. We found evidence of severe genetic bottlenecks, with effective population size dropping 85-91% after eradication, consistent with declines in population size. These rapid declines also led to a strong shift in the genetic structure of rats pre- and post-eradication campaign. Relatedness increased in two of the three study areas after eradication, suggesting reduced population sizes and uneven impacts of the campaign across colonies within the population. Lastly, dozens of low-frequency alleles (mean frequency of 0.037) observed before the campaign were undetected after the campaign, potentially lost from the population via drift or selection. We discuss the public health and ecological implications of these rapid genetic impacts of urban control efforts. Our data suggest that targeting the genetic viability of rat populations may be another important component for integrated pest management (IPM) strategies designed to reduce urban rats.